Lactate cross-feeding between Bifidobacterium species and Megasphaera indica contributes to butyrate formation in the human colonic environment - Zhao, Sainan (2024)
Butyrate, a physiologically active molecule, can be synthesized through metabolic interactions among colonic microorganisms. Previously, in a fermenting trial of human fecal microbiota, we observed that the butyrogenic effect positively correlated with the increasing Bifidobacterium population and an unidentified Megasphaera species. Therefore, we hypothesized that a cross-feeding phenomenon exists between Bifidobacterium and Megasphaera, where Megasphaera is the butyrate producer, and its growth relies on the metabolites generated by Bifidobacterium. To validate this hypothesis, three bacterial species (B. longum, B. pseudocatenulatum, and M. indica) were isolated from fecal cultures fermenting hydrolyzed xylan; pairwise cocultures were conducted between the Bifidobacterium and M. indica isolates; the microbial interactions were determined based on bacterial genome information, cell growth, substrate consumption, metabolite quantification, and metatranscriptomics. The results indicated that two Bifidobacterium isolates contained distinct gene clusters for xylan utilization and expressed varying substrate preferences. In contrast, M. indica alone scarcely grew on the xylose-based substrates. The growth of M. indica was significantly elevated by coculturing it with bifidobacteria, while the two Bifidobacterium species responded differently in the kinetics of cell growth and substrate consumption. Coculturing led to the depletion of lactate and increased the formation of butyrate. An RNA-seq analysis further revealed the upregulation of M. indica genes involved in the lactate utilization and butyrate formation pathways. We concluded that lactate generated by Bifidobacterium through catabolizing xylose fueled the growth of M. indica and triggered the synthesis of butyrate. Our findings demonstrated a novel cross-feeding mechanism to generate butyrate in the human colon. IMPORTANCE: Butyrate is an important short-chain fatty acid that is produced in the human colon through microbial fermentation. Although many butyrate-producing bacteria exhibit a limited capacity to degrade nondigestible food materials, butyrate can be formed through cross-feeding microbial metabolites, such as acetate or lactate. Previously, the literature has explicated the butyrate-forming links between Bifidobacterium and Faecalibacterium prausnitzii and between Bifidobacterium and Eubacterium rectale. In this study, we provided an alternative butyrate synthetic pathway through the interaction between Bifidobacterium and Megasphaera indica. M. indica is a species named in 2014 and is indigenous to the human intestinal tract. Scientific studies explaining the function of M. indica in the human colon are still limited. Our results show that M. indica proliferated based on the lactate generated by bifidobacteria and produced butyrate as its end metabolic product. The pathways identified here may contribute to understanding butyrate formation in the gut microbiota.